Pengaruh Etika Pustakawan Terhadap Pelayanan Prima Pada Perpustakaan - Noverista, Dinda Ivanny; Dewi, Laksmi; Hadiapurwa, Angga (Universitas Negeri Padang, 2022)
Librarian ethics in providing acceptable service is very important, where there are many impacts that are given to users when the services provided are deemed not good. Therefor the importance of librarians in having good ethics, solely to provide good service with good quality to users, so that users will feel satisfied with these services as explained by Prakoso (2015: 44) regarding ethics, explaining that This ethic for a person or a group of people makes the handle to regulate their behavior in accordance with the values and norms contained therein. Meanwhile, what is contained in the Law No. 47 of 2007 concerning Libraries. Explaining that 'library services are carried out in an excellent manner and are oriented towards the interests of the visitors. So excellent service in customer-oriented is the key to the quality of library services. 'Therefor the importance of having good ethics to provide good service with good quality.